1995
DOI: 10.1057/palgrave.jibs.8490848
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Success in International Strategic Alliances: Evidence from the Global Aerospace Industry

Abstract: International audienceThis paper presents the results of a study linking the performance of international joint ventures and alliances set up in the global aerospace industry to their strategic and organizational features. In a first stage, an empirically based taxonomy of the observed alliances is generated. Then, the economic performance of various types of alliances is evaluated on the basis of industry expert opinions, and the difference in performance of different alliance types is tested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
8

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(69 citation statements)
references
References 28 publications
1
60
0
8
Order By: Relevance
“…Referring to different theoretical backgrounds, the contributions of the studies analyzing interfirm antecedents of alliance performance center around critical success factors for managing alliances (e.g. Killing, 1983;Harrigan, 1986;Pekar and Allio, 1994;Dussauge and Garrette, 1995;Douma, 1997;Whipple and Frankel, 2000). In general, studies of this type suggest a set of success factors that considerably influence the performance of the dyadic relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to different theoretical backgrounds, the contributions of the studies analyzing interfirm antecedents of alliance performance center around critical success factors for managing alliances (e.g. Killing, 1983;Harrigan, 1986;Pekar and Allio, 1994;Dussauge and Garrette, 1995;Douma, 1997;Whipple and Frankel, 2000). In general, studies of this type suggest a set of success factors that considerably influence the performance of the dyadic relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The contrast between increasingly globalised networks (Bititci et al, 2012;Dussauge and Garrette, 1995) and the patchwork of IP laws (Geller, 1998;Peukert, 2012) amplifies the tensions in the appropriability-openness relationship. This contrast further spotlights the partner location dilemma (see Huang and Rice, 2013;Kotabe et al, 2008;Liu et al, 2013).…”
Section: Partner Locationmentioning
confidence: 99%
“…Indeed, the challenge of knowledge flows across firm boundaries has become even more evident due to the increasingly global character of inter-firm collaborations (Bititci et al, 2012;Dussauge and Garrette, 1995). This is because rising globalisation has made the tensions between globalised networks and the patchwork of national intellectual property (IP) laws more obvious (Geller, 1998;Peukert, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This view is supported by Blankenburg-Holm et al (1999) , who showed that mutual commitment increases mutual dependence, which in turn increases value creation. Stability is fundamental if the alliance is to last and develop successfully and deliver performance criteria ( Beamish and Inkpen, 1995 ;Dussauge and Garrette, 1995 ;Jiang et al , 2008 ). To date, little is known about which variables and factors impact on stability throughout the stages of alliance development ( Jiang et al , 2008 ).…”
Section: Common Causes For Problems and Obstaclesmentioning
confidence: 99%